Augmentation with an ovine forestomach matrix scaffold improves histological outcomes of rotator cuff repair in a rat model. Issue 1 (December 2015) - Street, Matthew; Thambyah, Ashvin; Dray, Michael; Amirapu, Satya; Tuari, Donna; Callon, Karen; McIntosh, Julie; Burkert, Kristina; Dunbar, P; Coleman, Brendan; Cornish, Jillian; Musson, David
Abstract Background Rotator cuff tears can cause significant pain and functional impairment. Without surgical repair, the rotator cuff has little healing potential, and following surgical repair, they are highly prone to re-rupture. Augmenting such repairs with a biomaterial scaffold has been suggested as a potential solution. Extracellular matrix (ECM)-based scaffolds are the most commonly used rotator cuff augments, although to date, reports on their success are variable. Here, we utilize pre-clinical in vitro and in vivo assays to assess the efficacy of a novel biomaterial scaffold, ovine forestomach extracellular matrix (OFM), in augmenting rotator cuff repair. Methods OFM was assessed in vitro for primary tenocyte growth and adherence, and for immunogenicity using an assay of primary human dendritic cell activation. In vivo, using a murine model, supraspinatus tendon repairs were carried out in 34 animals. Augmentation with OFM was compared to sham surgery and unaugmented control. At 6- and 12-week time points, the repairs were analysed biomechanically for strength of repair and histologically for quality of healing. Results OFM supported tenocyte growth in vitro and did not cause an immunogenic response. Augmentation with OFM improved the quality of healing of the repaired tendon, with no evidence of excessive inflammatory response. However, there was no biomechanical advantage of augmentation. Conclusions The ideal rotator cuff tendon augment has not yet been identified or clinically implemented. ECM scaffolds offer a promising solution to a difficult clinical problem. Here, we have shown improved histological healing with OFM augmentation. Identifying materials that offset the poorer mechanical properties of the rotator cuff post-injury/repair and enhance organised tendon healing will be paramount to incorporating augmentation into surgical treatment of the rotator cuff.